Voice changes associated with stress and distress in people living with diabetes: Results from the Colive Voice study - Charline Bour; Abir Elbéji; Dulce Canha; Noémie Topalian; Hanin Ayadi; Christelle Godin; Claire Guyon-Gardeux; Pierre-Yves Benhamou; Malvina Billères; Guy Fagherazzi (PLOS Digital Health, 2026)
Stress and diabetes distress impact glycemic control, self-care, and health outcomes in people living with diabetes, but current diabetes technologies lack easy-to-use, non-invasive methods to detect these states. The objective was to identify vocal features associated with stress and diabetes distress in people living with diabetes. Thus, we analyzed data from 679 adults with diabetes (381 women, 298 men), recruited via the global vocal biomarker screening platform Colive Voice . Participants recorded a standardized 30-second text. Vocal features were extracted using DisVoice across phonation, prosody, articulation, and phonological domains. Associations between vocal features and stress (self-reported, scale: 0–4) and diabetes distress (Problem Areas in Diabetes (PAID) questionnaire; categories: PAID